Thermosensitive hydrogel for cartilage regeneration via synergistic delivery of SDF-1α like polypeptides and kartogenin. (15th March 2023) - Yuan, Xi; Wan, Junlai; Yang, Yang; Huang, Long; Zhou, Chuankun; Su, Jin; Hua, Shuaibin; Pu, Hongxu; Zou, Yi; Zhu, Hao; Jiang, Xulin; Xiao, Jun
Abstract: Regeneration of injured articular cartilage is limited by low early-stage recruitment of stem cells and insufficient chondrogenic differentiation. Hydrogels are widely used to repair cartilage because they have excellent mechanical and biological properties. In this study, a dual drug-loaded thermosensitive hydroxypropyl chitin hydrogel (HPCH) system was prepared to release stromal-derived factor-1α-like polypeptides (SDFP) and kartogenin (KGN) for stem-cell recruitment and chondrogenic differentiation. The hydrogel had a network structure that promoted cell growth and nutrient exchange. Moreover, it was temperature sensitive and suitable for filling irregular defects. The system showed good biocompatibility in vitro and promoted stem-cell recruitment and chondrogenic differentiation. Furthermore, it reduced chondrocyte catabolism under inflammatory conditions. Animal experiments demonstrated that the dual-drug hydrogel systems can promote the regeneration of articular cartilage in rats. This study confirmed that an HPCH system loaded with KGN and SDFP could effectively repair articular cartilage defects and represents a viable treatment strategy.